Spine evaluation: Determination of the relationship between thoracic spinal deformity and sagittal curves by a noninvasive method - Dalva Minonroze Albuquerque Ferreira; Cíntia Girardi Fernandes; Marcela Regina Camargo; Célia Aparecida Stelluti Pachioni; Cristina Elena Prado Teles Fregonesi; Cláudia Regina Sgobbi Faria (Universidade Federal de Santa Catarina, 2010)
The objectives of this study were to compare sagittal plane alignment between subjects with spinal deformities and a group presenting no changes; to test the reliability of the tool used, and to determine the existence of correlations between spinal deformity and sagittal curvature measures. Forty young subjects were divided into two groups: a control group (n=20) presenting no changes or spinal deformity less than 0.5 cm in the dorsal curvature and 0.7 cm in the lumbar curvature, and an experimental group (n=20) with spinal deformities greater than those described for the control group. Spinal deformity and sagittal plane curvatures were measured using a water level-based tool and by the Adams test. Data were collected from the two groups on two distinct occasions. The Mann-Whitney test showed no difference between sampling times. A significant difference between the two groups was only observed in terms of cervical curvature. Spearman's test revealed a linear correlation between dorsal curvature and dorsal spinal deformity in the control group, between dorsal and lumbar curves in the two groups, and between dorsal spinal deformity and lumbar and sacral curves and between sacral curvature and dorsal and lumbar curves in the experimental group. In conclusion, spinal deformity measurement is associated with sagittal plane curvatures. The method proposed here is reliable, simple and accessible and can be reproduced without high costs and damage to the patient's health.